Mismatch negativity in methamphetamine dependence: a pilot study - Hosak, Ladislav; Kremlacek, Jan; Kuba, Miroslav; Libiger, Jan; Cizek, Jiri (Acta neurobiologiae experimentalis, 2008)
The objective of this study was to verify hypothesised changes in event related potentials (visual mismatch negativity, vMMN) in 17 subjects dependent on methamphetamine (MAMP) compared to age and gender matched 17 healthy volunteers. We found a significant correlation between vMMN and duration of methamphetamine abuse (Spearman correlation coefficient r=0.54-0.78; P<.05). The positive correlation indicates drop of originally more negative response to deviant stimulus, what may indicate a pre-attentive processing enhancement in the first years of MAMP abuse with its decease later on. Accordingly, post-hoc analysis revealed significantly stronger vMMN in patients with length of MAMP abuse shorter than 5 years than in paired controls. There were no such differences in abusers with the length of abuse longer than 5 years. The results show that the visual processing on the pre-attentional level can be influenced by long-term MAMP abuse, what can be specifically assessed by vMMN.
Keywords: Electroencephalography; poruchy spojené s užíváním amfetaminu; kontingentní negativní variace; Male; Contingent Negative Variation; Time Factors; psychofyzika; Psychophysics; mužské pohlaví; elektroencefalografie; studie případů a kontrol; regresní analýza; Adult; ženské pohlaví; Acoustic Stimulation; Humans; pilotní projekty; časové faktory; Pilot Projects; Evoked Potentials, Auditory; sluchové evokované potenciály; akustická stimulace; Amphetamine-Related Disorders; Regression Analysis; dospělí; Female; lidé; Case-Control Studies